Methylation of the chicken vitellogenin gene: influence of estradiol administration. - Meijlink, F C (1983)
The degree of methylation of the chicken vitellogenin gene has been investigated. Upon induction by administration of estradiol to a rooster, methyl groups at specific sites near the 5'-end of the gene are eliminated. The process of demethylation is slower than the activation of the gene. Demethylation is therefore probably not a prerequisite to gene transcription. At least two other sites in the coding region of the gene are methylated in the liver of estrogenized roosters, but not in the liver of a laying hen, where the gene is naturally active.